BANDWIDTH MODELING ON SMART CAMPUS BASED ON ENGINEERING METHOD – STATISTICS - Ismaredah , Ewi; Radiles , Hasdi (Kresnamedia Publisher, 2022)
The importance of generating internet traffic as one of the basic considerations in bandwidth allocation policies between faculties is increasing due to the number of students who complain about connection services on campus. This study proposes internet traffic generation based on the statistical - engineering method. The population is calculated based on class capacity in each faculty, as the main alibi of student attendance on campus where traffic arrivals are generated based on the arrival model through information on possible scheduling variations. Although internet services have different characteristics, they are physically determined by the bitrate and idle mode in the traffic time series. The results show recommendations in three application bitrate categories, namely 200kbps, 400kbps, and 800kbps Traffic Shaping. Keywords: , , ,